Disparities in Seroprevalence of SARS-CoV-2 Immunoglobulin Antibodies in a Large Midwestern Health Care System. (May 2021) - Fitzpatrick, Veronica; Rivelli, Anne; Blair, Christopher; Copeland, Kenneth; Richards, Jon
Objectives: Increased exposure to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) as a result of having an essential job is compounded by factors such as age, race, and ethnicity. We used a cross-sectional study design to describe disparities in the seroprevalence of SARS-CoV-2 immunoglobulin G (IgG) test results by demographic characteristics and clinical roles among a cohort of health care workers employed by the largest Midwestern health care system in the United States. Methods: We collected 16 233 SARS-CoV-2 IgG serum samples from June 8 through July 10, 2020, from a convenience sample of Illinois- and Wisconsin-based adult health care workers. The research team, in collaboration with ACL Laboratories, used a SARS-CoV-2 IgG assay to detect the presence of SARS-CoV-2 IgG antibodies. Study data included SARS-CoV-2 IgG assay results and demographic characteristics of workers (age, sex, race, ethnicity, clinical role, zip code). We generated crude and adjusted odds ratios (ORs) to describe disparities in seroprevalence distribution among demographic and social factors. Results: Of 16 233 IgG serum samples tested, 622 (3.8%) test results were positive for SARS-CoV-2. We found significant disparities in SARS-CoV-2 positivity by age, race, ethnicity, and clinical role. Participants aged 32-82 had lower adjusted ORs (aORs) of positive IgG than participants aged 18-31 (aOR range, 0.54-0.66). Odds of positivity were higher among Black (aOR = 3.86), Asian (aOR = 1.42), and mixed-race (aOR = 1.99) workers than among White workers; among Hispanic workers (aOR = 1.80) than among non-Hispanic workers; and among coronavirus disease 2019 (COVID-19) clinical workers (aOR = 1.86) than among nonclinical workers. Conclusions: Public health efforts should focus on increasing COVID-19 safety messaging, testing, vaccination, and other prevention efforts for people who are young, non-White, Hispanic, and working in COVID-19–clinical units.